REVIEW OF THE TREATMENT PROBLEM AND DRUG GROUPS FOR THE TREATMENT OF VIRAL HEPATITIS B (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Current treatment of chronic hepatitis B virus (HBV) infection, pegylated interferon-α (pegIFN-α) and nucleos(t)ide analogue (NA), can suppress HBV replication, reverse liver inflammation and fibrosis, and decrease risks of cirrhosis and hepatocellular carcinoma, but hepatitis B surface antigen (HBsAg) loss is rare. Functional HBV cure is defined as undetectable HBsAg and unquantifiable serum HBV DNA for at least 24 weeks after a finite course of therapy. This requires suppression of HBV replication and viral protein production as well as restoration of immune response to HBV. Direct-acting antivirals targeting virus entry, capsid assembly, viral protein production and secretion are in clinical trials. In parallel, immune modulatory therapies to stimulate HBV-specific immune response and to remove immune blockade are being tested. Clinical trials of direct-acting antivirals alone or immune modulatory therapies alone have not been successful in achieving HBV cure. Recent combinations of direct-acting antivirals and immune modulatory therapies have shown promising results particularly with combinations that included pegIFN-α. These results need to be confirmed in larger studies with longer follow-up, and further work is needed to develop simpler regimens with fewer drugs that can be administered orally and safely. While there is a strong desire to develop finite therapies that can achieve HBV cure, safety is paramount and new therapies must provide incremental value compared to standard of care, which is predominantly long-term NA therapy.